Be kind rewind [videorecording (DVD)] - Gondry, Michel; Black, Jack, 1969-; Mos Def (Rapper); Glover, Danny; Farrow, Mia, 1945- (New Line Home Entertainment, 2008)
Two local outcasts attempt to save a local video store. Amateur film director Mike must find a way to save the business after his magnetized friend, Jerry, erases every movie in the store. Using an outdated video camera and their own special effects, the two embark on an adventure to remake all the movies, from "Ghostbusters" to "Driving Miss Daisy," turning the two town misfits into local celebrities.